CHANGES IN HUMAN CAPITAL RESOURCES IN THE LABOUR MARKET IN POLAND FROM THE PERSPECTIVE OF THE EUROPEAN UNION AND OTHER COUNTRIES - Sawicka, Janina; Stolarczyk, Paulina (Acta Scientiarum Polonorum. Oeconomia, 2018)
The theoretical part of the paper presents conclusions from the literature review. The empirical part of the paper includes findings of the research carried out by the authors. Amending the human capital definition, based on the new approach from the perspective of equal opportunities, mainly for women, was the main aim and added value of the paper. Based on the previous research, authors hypothesized that the equality of opportunities in the labour market, social life, education and public life generates economic benefits, while the lack of such equality causes losses. To prove that the equality of opportunities enhances the value of human capital, the authors carried out their own research and referred to the findings of other empirical studies, data from the Central Statistical Office, Eurostat and expert opinions from such institutions as the European Institute for Equality of Women and Men in Vilnius (EIGE) and the World Economic Forum, OECD.